Diet selection in Arctic lemmings ( Lemmus sibericus and Dicrostonyx groenlandicus): food preferences - Rodgers, Arthur R.; Lewis, Martin C. (Canadian Journal of Zoology, 1985)
Testing of hypotheses relating lemming population dynamics to their food supply requires a detailed understanding of several major components of the diet selection process such as requirements, availability, preference, and selectivity. In this study, food preferences of Arctic lemmings were determined in cafeteria trials: Lemmus preferred graminoids and moss, while Dicrostonyx preferred shrubs and herbs. The stability of these preference patterns in each species was tested in further experimental cafeteria trials. Individuals of both species were pretreated on one of several diets, and two main types of trial were conducted involving limited and unlimited availability of test foods. Naive animals of both species, born and raised in captivity on artificial diets, were also used in the trials. In all cases, preference patterns in each species were maintained, suggesting that they are strongly heritable. Comparison of preference indices to the physical and chemical characteristics of tundra plants indicates that preference patterns in both species are related primarily to macronutrients and caloric content. Differences between Lemmus and Dicrostonyx are determined by secondary compounds and the physical characteristics of the plant species preferred by each. Comparison of ingestion rates and digestibility coefficients indicate that Dicrostonyx has a greater capacity than Lemmus in dealing with the negative characteristics of plants, such as secondary compounds or the presence of plant "hairs."